2020
DOI: 10.3390/molecules25081803
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Biological Entities from Human Blood by Using Magnetic Nanocomposites Obtained from Zeolite Precursors

Abstract: In this work, three novel magnetic metal–ceramic nanocomposites were obtained by thermally treating Fe-exchanged zeolites (either A or X) under reducing atmosphere at relatively mild temperatures (750–800 °C). The so-obtained materials were thoroughly characterized from the point of view of their physico-chemical properties and, then, used as magnetic adsorbents in the separation of the target gene factors V and RNASE and of the Staphylococcus aureus bacteria DNA from human blood. Such results were compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“… 16 Pathogen culture is often used to diagnose or evaluate the prognosis of sepsis, but its false positive is high and the diagnostic efficiency is undesirable. 17 It has been found that many kinds of lncRNAs are involved in the regulation of inflammation and the immune process, which can be used in the discrimination of sepsis. 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 Pathogen culture is often used to diagnose or evaluate the prognosis of sepsis, but its false positive is high and the diagnostic efficiency is undesirable. 17 It has been found that many kinds of lncRNAs are involved in the regulation of inflammation and the immune process, which can be used in the discrimination of sepsis. 18 …”
Section: Discussionmentioning
confidence: 99%
“…16 Pathogen culture is often used to diagnose or evaluate the prognosis of sepsis, but its false positive is high and the diagnostic efficiency is undesirable. 17 It has been found that many kinds of lncRNAs are involved in the regulation of inflammation and the immune process, which can be used in the discrimination of sepsis. 18 With the development of gene research technology, it has been found that lncRNAs have various functions and play crucial roles in many physiological processes and diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Adsorption of polyanionic HA on iron oxide nanoparticles and amino-silica-coated induces a zeta potential reversal in the acidic region; the negative charges on nanoparticles become gradually dominant. The reach of a negative surface over the entire pH (3)(4)(5)(6)(7)(8)(9)(10) interval indicates a complete coverage of the surface with humic acids. The maximum value of the negative zeta potential that can be achieved with an increase in the concentration of HA is 40 mV.…”
Section: Effects Of Ha Adsorption On Mnps Chargementioning
confidence: 99%
“…The magnetite nanoparticles (MNPs) have a wide range of applications, from the magnetic separation of technical media [1][2][3] to the preparation of polymer suspensions for biomedicine [4][5][6][7][8] and the life sciences [9]. The modification of MNPs with different species of stabilizing agents leads to producing monodispersed nanopowders and to supplying specific interactions with the molecules due to appropriate functional groups needed in various applications.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic separation (MS) is an increasingly significant technique for molecular biology. The MS technique is productive for purification at the commercial level [ 6 , 7 ]. Recently, target-specific magnetic nanocomposites (MNCs) have been developed which in conjugation with an adequate buffer system could make speedy and efficient purification.…”
Section: Introductionmentioning
confidence: 99%